(3eJWdHGJg, CTcGdg hCSGdjHg s - (3UdjMI (B, (3ZdGHs; (3Yjf ShjI(B, (3djdjGs ((3bSfWjfI (B:s (3efThQGJ CdaG ddhKGFb(B,s, 2020)
(3jYJHQ GdETgGQ GdGdcJQhfj ef CcKQ GdGfTWI GdJShjbjI GSJNOGeG aj eLGd GdJLGQI GdGdcJQhfjI, hefg JfGhd gPG GdcJGH ehVhY GdETgGQ GdGdcJQhfj ef fGMjI GdeJWdHGJ hGdGTcGd hGdCSGdjH, hbO Je JbSje gPg GdOQGSI Gdi GQHYI aUhd HgOa JSdjW GdVhA Ydi JWhQ GdETgGQ aj Vd GdJWhQGJ GdeSJeQI dJcfhdhLjG GdeYdheGJ hGdGJUGd, hPdc ef NdGd eMGhdI GdJYQa Ydi WHjYJg hYfGUQI , GdYhGed GdeSGYOI Ydi JWhQ GdGTgGQ GdGdcJQhfj , GVGaI Gdi GdJWQb Gdi XghQg hJWhQg , eJWdHGJ JWHjbg, hYjhHg heejRGJg, CSGdjHg hCTcGdg(B.s
(3HjHdjhZQGajG U(B.133 s
Keywords: (3GdETgGQ GdGdcJQhfjs